PERCEPTION OF PEOPLE WITH CHRONIC CONDITIONS AND THE INFLUENCE ON THE INJURY HEALING PROCESS - de Faveri Ferreira, Vanessa; da Cruz, Osvaldo Luiz Schreiner; Lima, Daniella Karine Souza; da Costa, Antonielle Moreira Dutra; de Barros, Gabriela Rita; Pitchinin, Gabrieli; Zanini, Vanderson Rodrigo; da Rosa, Marilei Tarciane (Seven Editora, 2025)
The study aimed to analyze the perceptions of people with chronic diseases regarding the healing of hard-to-heal wounds. Most participants recognized the influence of their chronic condition but only received proper guidance after being referred to specialized care. Popular practices were common, along with difficulties related to diet, medication, and self-care. It is concluded that care must be comprehensive, with a focus on health education and strengthening of primary care. DOI: https://doi.org/10.56238/sevened2025.029-084